Bangsa Melayu Malay concepts of democracy and community, 1945-1950 - Ariffin Omar (Strategic Information and Research Development Centre, 2015)
In this new edition of a classic book, Ariffin Omar focuses on the basic differences in thinking, temperament and attitude between the two groups of Malays which led to markedly different political outcomes. It will be of enormous appeal to all those interested in the history of ideas and the politics of ethnicity.